Novel O-band tunable fiber laser using an array waveguide grating - Ahmad, Harith; Zulkifli, Mohd Zamani; A. A., Latif; S.W., Harun (WILEY-VCH Verlag GmbH & Co. KGaA, 2010)
A novel tunable fibre laser (TFL) operating in the ordinary band (O-band) of 1310 nm is proposed and demonstrated. The proposed TFL is developed using a 1×16 arrayed waveguide grating (AWG) as a slicing mechanism for the broadband amplified spontaneous emission (ASE) source and an optical channel selector (OCS) to provide the tunability. A semiconductor optical amplifier (SOA) with a centre wavelength of 1310 nm serves as the compact gain medium for the TFL and also as a broadband ASE source. The TFL has a tuning range of 1301.26 nm to 1311.18 nm with 9.92 nm span and a channel spacing of 0.7 nm. The measured output power is about –4 and –8 dBm and with a side node suppression ratio (SMSR) of 29 to 33 dB.